(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The grounds for the creation, change and cancellation of civil rights and duties are usually determined at the legislative level. What these actions consist of as a rule is systematized and cited in Article 8 of the Civil Code. According to the first part of this article, civil rights and duties arise from the foundations of legislation and the actions of individuals. Only these actions should create rights and duties "according to the general principles and content of the legislation".